2018
DOI: 10.29019/enfoqueute.v9n2.195
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and spatio-temporal dynamics of Cylindrospermopsis raciborski in an Amazonian Lagoon, Ecuador.

Abstract: The cyanobacteria Cylindrospermopsis raciborskii, is a fresh water ubiquitous species from tropical to temperate weather. It is potentially capable of producing toxins.  Thus it is necessary to monitor its presence in fresh waters associated to recreational use activities and human consumption. There are official reports and one thesis reporting the presence of C. raciborskii in Ecuador. Nevertheless, this country does not appear in the latest distribution maps of this species in the scientific literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Limoncocha Lagoon also fulfills the environmental conditions for this species to bloom (Mowe et al, 2015;Padisák, 1997;Padisák & Reynolds, 1998;Whitton & Potts, 2002), as it is highly eutrophicated due to natural processes and sewage from nearby Limoncocha village and has a temperature ranging from 28 °C to 32.23 °C (Gómez Durañona, 2005). The presence of cyrE from R. raciborskii sample in this lagoon was consistent with the report of this cyanobacterium by Venegas et al (2018). Mojanda Lagoon, where also cyrE1 sequence was detected, is located at 3,710 m asl with an average temperature of approximately 13.5 ºC, this lagoon is mesotrophic due to anthropic activities such as livestock.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Limoncocha Lagoon also fulfills the environmental conditions for this species to bloom (Mowe et al, 2015;Padisák, 1997;Padisák & Reynolds, 1998;Whitton & Potts, 2002), as it is highly eutrophicated due to natural processes and sewage from nearby Limoncocha village and has a temperature ranging from 28 °C to 32.23 °C (Gómez Durañona, 2005). The presence of cyrE from R. raciborskii sample in this lagoon was consistent with the report of this cyanobacterium by Venegas et al (2018). Mojanda Lagoon, where also cyrE1 sequence was detected, is located at 3,710 m asl with an average temperature of approximately 13.5 ºC, this lagoon is mesotrophic due to anthropic activities such as livestock.…”
Section: Resultssupporting
confidence: 91%
“…The closest match to the cyrE2 sequence at the GenBank was 98% identity to cyrE related to Aphanizomenon sp., which has been described as a benthic cyanobacterium genus (Gaget et al, 2017). In South America, most isolated strains from R. raciborskii are reported to produce saxitoxins (Hoff-Risseti et al, 2013), although CN producers have also been found in Brazil and Venezuela (Antunes et al, 2015;Mowe et al, 2015), and Ecuador (Ballesteros et al, 2021;Van Colen et al, 2017;Venegas et al, 2018). Even though R. racibosrkii has been reported in Yahuarcocha and San Pablo in association with the presence of CN (Van Colen et al, 2017), cyrJ was not amplified from samples in these water bodies.…”
Section: Resultsmentioning
confidence: 99%